Application of Path Analysis to Modeling from Population-based Data Sources - Heru Santoso Wahito Nugroho; Teuku Alamsyah; Angelito E. Alvarado (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2022)
In research on statistical modeling, researchers generally use sample-based data, but in a less frequent proportion, there are also researchers who use population-based data. For this second group, the researcher should not use the p-value as a basis for deciding the effect between variables, because this method is only suitable for sample-based modeling. For modeling using population-based data, researchers cannot use p-values, so meaningfulness should be used to determine the influence between variables. In this case, the minimum value of the path coefficient that is considered meaningful is 0 . Keywords: modeling; path analysis; population-based; meaningfulness